Tryptophan Metabolism and COVID-19-Induced Skeletal Muscle Damage: Is ACE2 a Key Regulator? - Takeshita, Hikari; Yamamoto, Koichi (Frontiers in Nutrition, 2022)
The severity of coronavirus disease 2019 (COVID-19) is characterized by systemic damage to organs, including skeletal muscle, due to excessive secretion of inflammatory cytokines. Clinical studies have suggested that the kynurenine pathway of tryptophan metabolism is selectively enhanced in patients with severe COVID-19. In addition to acting as a receptor for severe acute respiratory syndrome coronavirus 2, the causative virus of COVID-19, angiotensin converting enzyme 2 (ACE2) contributes to tryptophan absorption and inhibition of the renin-angiotensin system. In this article, we review previous studies to assess the potential for a link between tryptophan metabolism, ACE2, and skeletal muscle damage in patients with COVID-19.